Development of Physics Learning Tools Based on the STEM-Creative Problem Solving Model to Increase Students' Scientific Literacy and Creativity - Busyairi, Ahmad; Harjono, Ahmad; A, Syahrial; Taufiq, Muhammad; Ardhuha, Jannatin; Hasan, Yulia (Universitas Hamzanwadi, 2023)
Scientific literacy and creativity are two of several competencies that are very important to have now and in the future. However, referring to the data released by TIMSS and the results of previous research, shows that the scientific literacy and creativity of students in Indonesia are both low. This research aims to develop a STEM-Creative Problem Solving model learning tool to increase students' scientific literacy and creativity. This type of research is research & development. The development procedure in this research uses a 4D mode; define, design, develop, and disseminate. The instrument for knowing expert assessments of learning tools that have been developed uses validation sheets. From the results of the assessment of 3 (three) experts, it shows that the learning tools that have been developed have high validity with an average score for learning plans of 3.83 and an average validity score for student worksheets of 3.81. Thus, it can be concluded that the learning tools that have been developed are suitable to be continued to the limited trial stage (effectiveness test) and disseminated widely.